Work Motivation of Accountants : The Case of Accounting Service Firms in Hanoi, Vietnam - Duc Tai Do; Thi Huong Nguyen; Thi Xuan Nguyen (Lembaga Penerbit Fakultas Ekonomi dan Bisnis Universitas Trisakti, 2019)
The main objective of this study was to identify, evaluate, and to measure the attributes of work motivation of accountants in the accounting service firms in Hanoi. The study was based on a field survey using a semi-structured questionnaire on a sample of 150 accountants. But, only 120 filled questionnaires were satisfactory and therefore included in the analysis. By using seceral statistical analytical tools, i.e. descriptive statistics, Cronbach’s Alpha analysis, Independent Ttest and ANOVA, the study has identified and measured eight (8) attributes of work motivation that have great effects on employees (or in this case study, accountants). Based on the findings, some recommendations are given for accountants and accounting service firms to improve the work motivation of accountants.